2021
DOI: 10.33140/coa.06.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Renin Activity after Diuretic Treatment in Patients with Stable Heart Failure: With Special Reference to its Association with Electrolyte Chloride

Abstract: A recent study reported an intimate association between urinary chloride (Cl) and plasma renin activity (PRA) in acute heart failure (HF) status, reflecting normal functioning of the ‘tubulo-glomerular feedback’ mechanism. Whether the ‘tubuloglomerular feedback’ mechanism functions normally in stable HF status, however, is unclear. This study examined whether the ‘tubulo-glomerular feedback’ mechanism functions normally under resolution of worsening HF after decongestive therapy. Data from 26 patients with acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, hypochloremia in turn induces renin secretion, increases the expression and activity of sodium-potassium-chloride cotransporters as well as sodium-chloride cotransporters, and promotes electrolytes reabsorption leading to diuretic resistance ( 25 ). Several studies have demonstrated that low serum chloride is apparently associated with neurohormonal activation and diuretic resistance, leading to impaired decongestive diuretic efficacy in patients with heart failure, which in turn increases the risk of death and readmission ( 26 , 27 ). This may be a common consequence of hypochloremia.…”
Section: Discussionmentioning
confidence: 99%
“…However, hypochloremia in turn induces renin secretion, increases the expression and activity of sodium-potassium-chloride cotransporters as well as sodium-chloride cotransporters, and promotes electrolytes reabsorption leading to diuretic resistance ( 25 ). Several studies have demonstrated that low serum chloride is apparently associated with neurohormonal activation and diuretic resistance, leading to impaired decongestive diuretic efficacy in patients with heart failure, which in turn increases the risk of death and readmission ( 26 , 27 ). This may be a common consequence of hypochloremia.…”
Section: Discussionmentioning
confidence: 99%